Personalized recognition system in online shopping by using deep learning - Devarakonda Venkata, Manjula; Donda, Prashanth; Madhavi, N. Bindu; Parkash Singh, Pavitar; Jaisudhan Pazhani, A. Azhagu; Rehana Banu, Shaik (EAI Endorsed Transactions on Internet of Things, 2024)
This study presents an effective monitoring system to watch the Buying Experience across multiple shop interactions based on the refinement of the information derived from physiological data and facial expressions. The system’s efficacy in recognizing consumers’ emotions and avoiding bias based on age, race, and evaluation gender in a pilot study. The system’s data has been compared to the outcomes of conventional video analysis. The study’s conclusions indicate that the suggested approach can aid in the analysis of consumer experience in a store setting.